Improving TCP Performance over Mobile Networks. - Elaarag, Hala (ACM computing surveys.)
Transmission Control Protocol (TCP) is the most commonly used transport protocol on the Internet. All indications assure that mobile computers and their wireless communication links will be an integral part of the future internetworks. In this paper, we present how regular TCP is well tuned to react to packet loss in wired networks. We then define mobility and the problems associated with it. We discuss why regular TCP is not suitable for mobile hosts and their wireless links by providing simulation results that demonstrate the effect of the high bit error rates of the wireless link on TCP performance. We discuss and illustrate the problems caused by the mobility of hosts using a graph tracing packets between fixed and mobile hosts. We then present a survey of the research done to improve the performance of TCP over mobile wireless networks. We classify the proposed solutions into three categories: link layer, end-to-end and split. We discuss the intuition behind each solution and present example protocols of each category. We discuss the protocols functionality, their strengths and weaknesses. We also provide a comparison of the different approaches in the same category and on the category level. We conclude this survey with a recommendation of the features that need to be satisfied in a standard mobile TCP protocol.